Results of a New Treatment Protocol for Sudden Sensorineural Hearing Loss Using Betamethasone for Intratympanic Therapy - Lopes, Paula Tardim; Almeida, Jessica; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2024)
Introduction Sudden sensorineural hearing loss (SSNHL) is defined as a rapid sensation of hearing impairment in one or both ears. Based on its personal impact on patients, the present study advances the analysis of new treatments for the prompt recognition and management of SSNHL, with higher chances of improvements in terms of hearing recovery and quality of life of the patients.Objective To describe the intratympanic (IT) corticoid infiltration technique, to demonstrate the efficacy of betamethasone injection as a sequential treatment in patients whose initial systemic steroid treatment failed, as well as to compare its use in different treatment periods.Methods The present clinical trial was conducted with 37 patients referred to our office with the diagnosis of SSNHL, from September 2019 to May 2022, who provided informed consent to participate.Results Even dividing the analysis of increasing the pure tone average (PTA) or speech recognition threshold (SRT) between the difference into initiation of the salvage therapy in up to 15 days of the sudden deafness event, and between 15 days and 3 months of the event, we did not find any difference in hearing improvement.Conclusion Intratympanic corticosteroid therapy is prescribed when conventional therapy fails or when there is a limitation to the use of corticosteroids due to the presence of systemic disorders. As such, new drugs, such as bethametasone, are studied and show promising results.
Keywords: hearing loss; sensorineural hearing loss; sudden; salvage therapy steroids; betamethasone